1996
DOI: 10.3758/bf03213099
|View full text |Cite
|
Sign up to set email alerts
|

The visual perception of rigid motion from constant flow fields

Abstract: Four experiments investigated observers' judgments of rigidity for different types of optical motion. The depicted structural deformations were of two types: (1) those with nonparallel image trajectories that are detectable from the first-order spatiotemporal relations between pairs of views; and (2) those with parallel image trajectories that can only be detected from higher order relations among three or more views. Patterns were composed of smooth flow fields in Experiments 1 and 3, and of wire frame figure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 28 publications
(55 reference statements)
3
30
1
Order By: Relevance
“…This point can be illustrated by considering the case of a constant optic flow (see Perotti, Todd, & Norman, 1996). In the case of Figure 2b, for example, the models described earlier predict a constant surface slant, because the gradient x at any moment is constant.…”
Section: Long-term Temporal Integrationmentioning
confidence: 92%
“…This point can be illustrated by considering the case of a constant optic flow (see Perotti, Todd, & Norman, 1996). In the case of Figure 2b, for example, the models described earlier predict a constant surface slant, because the gradient x at any moment is constant.…”
Section: Long-term Temporal Integrationmentioning
confidence: 92%
“…The sliding sleeve transformation would yield a constant flow display-that is, a structure-from-motion display in which the optic flow at any given point in the image would be constant. Perotti, Todd, and Norman (1996) used constant flow displays to investigate whether human observers use information available over more than two frames-that is, greater than first-order flow. They found that observers did not and, thus, that observers could not distinguish nonrigid constant flow from rigid rotation.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have attempted to deduce the minimum number of views and number of elements that are required by the visual system to detect nonrigidity from parallel projections (Braunstein, Hoffman, & Pollick, 1990;Braunstein et al, 1987;Norman & Todd, 1993;Perotti, Todd, & Norman, 1996;Todd, 1982;Todd & Bressan, 1990). These experiments show that various types of nonrigidity are detectable with the theoretical minimum number ofelements and views.…”
mentioning
confidence: 99%
“…He determined the impact that various changes in these characteristics have on the human ability to judge whether the objects move rigidly or not. In experiments done by Norman and Todd (1993) and Perotti et al (1996), human perception of rigidity appears to have been determined primarily by first-order temporal relations available in two frames, although in some cases higher order temporal relations seem to have been used. In our experiments, we explore this issue further.…”
mentioning
confidence: 99%